2016
DOI: 10.17511/ijmrr.2016.i08.26
|View full text |Cite
|
Sign up to set email alerts
|

Microbial profile and risk factors of central venous catheter associated blood stream infections in Tertiary Care Hospital, Amritsar

Abstract: Introduction: Central venous catheter (CVC) related blood stream infections are associated with serious infectious complications resulting in significant morbidity, increased duration of hospitalization and added medical cost. Aim: The study was done to determine the incidence of central venous catheter related infections, their antimicrobial sensitivity pattern, biofilm production and associated risk factors in hospitalized patients. Material and Method: Catheter tip culture & blood cultures of 143 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is also possible that infection control procedures at Apeksha Hospital contributed to the lower CRBSI rate. Oberoi et al 15 suggested this irregularity of the incidence of CRBSI in various studies could be due to factors such as site of catheterisation, insertion techniques used, type(s) of catheter used, catheter care techniques and diagnostic criteria used to diagnose CRBSI.…”
Section: Causative Organisms and Antibiotic Susceptibilitymentioning
confidence: 99%
“…It is also possible that infection control procedures at Apeksha Hospital contributed to the lower CRBSI rate. Oberoi et al 15 suggested this irregularity of the incidence of CRBSI in various studies could be due to factors such as site of catheterisation, insertion techniques used, type(s) of catheter used, catheter care techniques and diagnostic criteria used to diagnose CRBSI.…”
Section: Causative Organisms and Antibiotic Susceptibilitymentioning
confidence: 99%
“…Oberai et al in their study published in this issue discussed that Bloodstream infections related to the use of central venous catheters are an important cause of patient morbidity, mortality, and increased health care costs. Their study highlights the predominance of multidrug resistant gram negative organisms which were also found to be biofilm producers [10].…”
mentioning
confidence: 99%